Complete Genome Sequences of Four Isolates of Vancomycin-Resistant Enterococcus faecium with the vanA Gene and Two Daptomycin Resistance Mutations, Obtained from Two Inpatients with Prolonged Bacteremia - Jenjaroenpun, Piroon (Microbiol Resour Announc, 2020)
Here, we present complete genome sequences of four Enterococcus faecium isolates, obtained from two patients with apparent vancomycin-resistant Enterococcus faecium bacteremia; these isolates also carried two mutations known to be associated with daptomycin resistance. Sequences were obtained using de novo and hybrid assembly of Oxford Nanopore and Illumina sequence data.